The Availability and completeness of funder metadata in Crossref: A case study for publications funded by the Dutch Research Council NWO - de Jonge, Hans; Kramer, Bianca (Septentrio Conference Series, 2022)
Research funders spend considerable efforts on collecting information about the outcomes of the research they fund. Publications are amongst important data they collect because these represent direct results of research funding. To help funders track publication output associated with their funding, Crossref initiated the Fundref project in 2013, enabling publishers to deposit funding information using persistent identifiers. Currently, 25% of articles published in 2021 have funder metadata. However, it is hard to assess that figure because it is not known how many articles are the result of funded research and therefore should include funder metadata. In this poster we present the outcomes of a study in which we try to assess the availability and completeness of funding information in Crossref. For this analysis we made use of a subset of publications of which we are certain that they are the result of funding provided by a specific funding agency (the Dutch Research Council NWO) and therefore – in theory – should contain funding information. We also compared our findings with the availability of funding information in the larger (commercial) databases. Only 67% of the 5004 articles in our dataset contain funding information in Crossref, with a subset acknowledging NWO as funder name and/or Funder IDs linked to NWO (53% and 45%, respectively). Web of Science (WoS), Scopus and Dimensions are all able to infer additional funding information from funding statements in the full text of the articles. Funding information in Lens largely corresponds to that in Crossref, with some additional funding information likely taken from PubMed. We observe interesting differences between publishers in the coverage and completeness of funding metadata in Crossref compared to proprietary databases, highlighting the need for publishers to step up their efforts to collect this data and submit to Crossref. The open unrestricted availability of structured, machine readable information about the funding of research is important for multiple reasons. Important progress has been made in recent years to promote the open availability of metadata of the scholarly record. Our research shows that the open availability of funding information, while increasing, also needs improvement.